2010 International Conference on Machine Vision and Human-Machine Interface 2010
DOI: 10.1109/mvhi.2010.28
|View full text |Cite
|
Sign up to set email alerts
|

The Research on Process of Deep Cryogenic Treatment for YT15 Carbide Insert

Abstract: Deep cryogenic treatment (DCT) is a one time permanent process. In DCT, the material is slowly cooled down to the soaking temperature, is held at soaking temperature for a period time, and is heated back to room temperature. DCT process factors have their own effect on the mechanical properties of material. The paper studies the deep cryogenic treatment process of YT15 carbide inserts by orthogonal experiment method, and analyses the effects of various cryogenic treatment process parameters on mechanical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…They have proved this by performing cylindrical turning using untreated and treated inserts. Yan et al [8] observed a rise in the hardness and wear resistance of tungsten carbide inserts that were treated cryogenically. Similar improvement in the wear resistance was also observed by Dinesh et al [9].…”
Section: Introductionmentioning
confidence: 99%
“…They have proved this by performing cylindrical turning using untreated and treated inserts. Yan et al [8] observed a rise in the hardness and wear resistance of tungsten carbide inserts that were treated cryogenically. Similar improvement in the wear resistance was also observed by Dinesh et al [9].…”
Section: Introductionmentioning
confidence: 99%